Management Values, Resources and Power: A comparison of Management Values in Ålesund and Vaasa Hospitals - Håvold, Ole Kristian Sandnes (My University, 2009)
There are many papers out on the efficiency of Finnish public hospital system and there are several news stories in Norway about this. However I have yet to see one focusing on management values in Finland compared to other public hospital systems. In this thesis two hospitals will be focused on, one in each country. Furthermore it will look at these values and how these two hospitals compare to each other. First focusing on what are the differences and similarities in the softness and hardness of managerial values, and secondly is it possible to link this difference in managerial values to the management of Ålesund and Vaasa hospital? The theoretical framework is based on Hofstede's MAS index, McGregor's theory X and Y and managerial powers which are used to convey orders and to which extent the employees share their managers’ opinions about themselves and the system. This is done through interviews as well as questionnaires in a triangulation to find where these countries fall on a scale of hard to soft values. Both the empirical data and statistical data have been collected by thesis writer. This study shows that there are softer values in Norway, but not as much as one would have expected by looking at Hofstede's MAS index. There are indications that the structure of the system is flatter in Norway as well. The managerial powers which are in effect also differ, but only slightly showing that there is some sort of structure in place limiting the use of certain powers. Finally this study finds that the level of work satisfaction is higher in Norway, and that lack of resources plagues both sides, in different ways, personnel in Finland and money is Norway. That Finland's health care system is more efficient that the Norwegian is true, but it seems to come at the cost of work satisfaction and recruitment of personnel.
Keywords: Health care; Welfare state; Managerial Powers; Hospital Value Management; masculinity index; Theory X and Y; fi=Public Administration|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|